Customer Service Quality in the Utilities Sector: Sustainability Perspective - Salkauskiene, Ligita; Balvociute, Rasa (European Journal of Sustainable Development, 2025)
The article presents a study on customer service quality in Lithuanian utility companies. To survive in the long term, changes related to economic, social, and environmental requirements are necessary; the implementation of sustainability is essential. Growing expectations of stakeholders are the need for companies to move towards sustainability and become sustainable. The analysis of human resource competencies required for sustainable service provision is a field of modern scientific research. The study focuses on enhancing customer service, which is defined as a philosophy that incorporates sustainability dimensions. The analysis of research data distinguishes the key principles of sustainable customer service: cooperation, involvement, loyalty, quality of service provision, and competence. The aim is to investigate how organizations providing utility services serve their customers, assess the quality of customer interactions, and identify trends in the implementation of sustainability principles. The research objectives are as follows: to analyze the principles of sustainability and the criteria for evaluating customer service; to evaluate changes in the quality of customer service provided by utility organizations from 2015 to 2024 and explore prospects. Keywords: Service of customers, sustainability, service quality, quality management, human resources management.